Transmission of modified JPEG images through AWGN channel. (29th June 2009) - Vasuki, A.; Vanathi, P.T.
Joint Photographic Experts Group (JPEG) is a standard for compressing continuous-tone images. In this paper, image is compressed based on JPEG, but in place of Huffman coding, Run Length Encoding (RLE)/Vector Quantisation (VQ) has been applied and performance evaluated. RLE does not require table storage, but produces lesser compression than Huffman. VQ achieves higher compression at the cost of reduced quality. Further, the reconstructed image has been filtered to reduce blocking artifacts. When the encoded image is corrupted with Additive White Gaussian Noise (AWGN), VQ is more robust than Huffman/RLE since it is fixed-length encoding technique.